ENRICHING STUDENTS’ VOCABULARY THROUGH MATCHING GAME AT SECOND GRADE STUDENTS OF MA PUTRA AL-ISLAHUDDINY KEDIRI LOMBOK BARAT IN ACADEMIC YEAR 2018/2019 - Muhammad Sarifuddin; Terasne Terasne (Realita : Jurnal Bimbingan dan Konseling, 2018)
This research is aimed at finding out wheather Matching Game able to enrich students’ vocabularies mastery at second grade students of MA Putra Al-Islahuddiny Kediri Lombok Barat  in academic year 2018/2019. This study has conducted to find out the Effect  of Matching Game toward  Students’  Vocabulary mastery  at MA Putra AL-Islahuddiny Kediri in Academic Year 2018/2019. This research used Experimental approach. For more detail, This research categorized as a quasi-experimental reserch. This research   used Randomized Two-Groups Posttest Design only, the two-group experimental design may involve little more than random assignment and a posttest. The population of this research was the second  grade students of MA Putra Al-Islahuddiny Kediri Lombok Barat in Academic Year 2018/2019. The total numbers of the students was 67 students that consist of three classes namely VIIA (23 students), VIIB (23 students) and VIIC (24 students). In this case writer used cluster random sampling to select the intact group. The researcher took 2 classes as sample, those were class VIIA (23 students) as experimental group and class VIIB (23 students) as control group. Both of the classes are determined by lottery. The data of this research collected through Pre-test and post-test. The collected data then analyzed through analyzing the Mean, Mode, Median and Standard Deviation. After that the result of the Mean, Mode, Median and Standard Deviation have analyzed inferentially. Base on the computation of t- test of independent sample, the value of  is 3,14 and the value of   is 1,677 from (df) 48 in degree of significance 5%, because  3,14 >  1,677  it can be concluded that Ha (alternative hypothesis) is accepted, it means that matching game is able to enrich students’ vocabulary.